Utilization-focused evaluation for agricultural innovation - Patton, M.Q.; Horton, Douglas (2009)
Utilization-focused evaluation (UFE) is based on the principle that an evaluation should be judged by its utility. So no matter how technically sound and methodologically elegant, an evaluation is not truly a good evaluation unless the findings are used. UFE is a framework for enhancing the likelihood that evaluation findings will be used and lessons will be learnt from the evaluation process. This Brief, based on the book Utilization-focused evaluation, introduces this approach to evaluation, outlines key steps in the evaluation process, identifies some of the main benefits of UFE, and provides two examples of UFE in the context of programmes aimed at promoting agricultural innovation.